Assessing Chemical Diversity in Psilotum nudum (L.) Beauv., a Pantropical Whisk Fern That Has Lost Many of Its Fern-Like Characters - Šamec, Dunja; Pierz, Verena; Srividya, Narayanan; Wüst, Matthias; Lange, B. Markus (Frontiers in Plant Science, 2019)
Members of the Psilotales (whisk ferns) have a unique anatomy, with conducting tissues but lacking true leaves and roots. Based on recent phyogenies, these features appear to represent a reduction from a more typical modern fern plant rather than the persistence of ancestral features. In this study, extracts of several Psilotum organs and tissues were analyzed by Gas Chromatography – Mass Spectrometry (GC-MS) and High Performance Liquid Chromatography – Quadrupole Time of Flight – Mass Spectrometry (HPLC-QTOF-MS). Some arylpyrones and biflavonoids had previously been reported to occur in Psilotum and these metabolite classes were found to be prominent constituents in the present study. Some of these were enriched and further characterized by Nuclear Magnetic Resonance (NMR) spectroscopy. HPLC-QTOF-MS and NMR data were searched against an updated Spektraris database (expanded by incorporating over 300 new arylpyrone and biflavonoid spectral records) to aid significantly with peak annotation. Principal Component Analysis (PCA) with combined GC-MS and HPLC-QTOF-MS data sets obtained with several Psilotum organs and tissues indicated a clear separation of the sample types. The principal component scores for below-ground rhizome samples corresponded to the vectors for carbohydrate monomers and dimers and small organic acids. Above-ground rhizome samples had principal component scores closer to the direction of vectors for arylpyrone glycosides and sucrose (which had high concentrations in above-and below-ground rhizomes). The unique position of brown synangia in a PCA plot correlated with the vector for biflavonoid glycosides. Principal component scores for green and yellow synangia correlated with the direction of vectors for arylpyrone glycosides and biflavonoid aglycones. Localization studies with cross sections of above-ground rhizomes, using Matrix-Assisted Laser Desorption/Ionization – Mass Spectrometry (MALDI-MS), provided evidence for a preferential accumulation of arylpyrone glycosides and biflavonoid aglycones in cells of the chlorenchyma. Our results indicate a differential localization of metabolites with potentially tissue-specific functions in defenses against biotic and abiotic stresses. The data are also a foundation for follow-up work to better understand chemical diversity in the Psilotales and other members of the fern lineage.